Unusual appearance of mother-of-pearl clouds above El Calafate, Argentina (50°21′S, 72°16′W) - Dörnbrack, Andreas; Kaifler, Bernd; Kaifler, Natalie; Rapp, Markus; Wildmann, Norman; Garhammar, Markus; Ohlmann, Klaus; Payne, James, M.; Sandercock, Morgan; Austin, Elisabeth, J. (Weather, 2020)
Visual observations from the ground and from a glider soaring in the lowermost stratosphere revealed the existence of stratospheric mother-of-pearl clouds above El Calafate in the lee of the Andes on 11 September 2019. The appearance of these clouds is rather unusual considering the time – end of the austral winter – and the location at about 50°S, being far away from Antarctica. This paper presents the available observations and describes the overall meteorological situation that was related to the earliest sudden stratospheric warming recorded so far in the Southern Hemisphere. By using high-resolution numerical simulations, we show evidence of mountain waves propagating up to the stratosphere that are responsible for generating the localised cold stratospheric temperature anomalies required for ice cloud formation. Snapshots of a mother-of-pearl cloud from the camera installed at the PERLAN 2 aircraft's tail wing.